Heterosis Analysis in Pumpkin (Cucurbitamoschata Duch. Ex. Poir) - Md Mohsin, Gazi; Rahman, Md Sajedur; Ahamed, Farruk; Md Hasanuzzaman, - (Dhaka University Journal of Biological Sciences, 2022)
The research was carried out at Lal Teer Seed Ltd. Gazipur to determine the heterosis of yield and yield contributing traits of pumpkin (Cucurbita moschata Duch. ex Poir.). Six diverse pumpkin parents (viz. CM-1, BARI Mistikumra-1, CM-20 and CM-8) and their 30 F1 hybrids derived from 6X6 diallel including reciprocal were used as research materials. Thirteen genetic parameters [viz. days to first male flower opening, days to first female flower opening, number of flowers (male and female) per plant, fruit length and diameter (cm), fruit weight (kg), flesh thickness (cm), brix (%), number of fruits per plant, number of seeds per fruit, 100-seeds weight (g), yield per plant (kg)] were estimated. The results revealed significantly higher and positive heterosis and expected negative effects for different important characters of pumpkin. The two cross combinations namely; CM-1 × BARI Mistikumra-1 and CM-8 × CM-1 were identified as the promising hybrids which showed the significant higher heterosis, heterobeltiosis and standard heterosis. These finding suggest that cross combinations of indigenous x exotic parents may be beneficial for fruit yield, particularly when used as commercial hybrids. The results showed that these two combinations gave the most promising hybrids (F1), so these two F1 lines were registered in National Seed Board (NSB) of Bangladesh as Hajee F1 and Danesh F1 hybrid varieties. Dhaka Univ. J. Biol. Sci. 31(1): 117-136, 2022 (January)